Age-Specific Cut-off Values of Amino Acids and Acylcarnitines for Diagnosis of Inborn Errors of Metabolism Using Liquid Chromatography Tandem Mass Spectrometry. (6th January 2019) - Sarker, Suprovath Kumar; Islam, Md Tarikul; Biswas, Aparna; Bhuyan, Golam Sarower; Sultana, Rosy; Sultana, Nusrat; Rakhshanda, Shagoofa; Begum, Mst. Noorjahan; Rahat, Asifuzzaman; Yeasmin, Sharmina; Khanam, Mowshori; Saha, Asim Kumar; et al.
Abstract : Liquid Chromatography tandem mass spectrometry (LC-MS/MS) is used for the diagnosis of more than 30 inborn errors of metabolisms (IEMs). Accurate and reliable diagnosis of IEMs by quantifying amino acids (AAs) and acylcarnitines (ACs) using LC-MS/MS systems depend on the establishment of age-specific cut-offs of the analytes. This study aimed to (1) determine the age-specific cut-off values of AAs and ACs in Bangladesh and (2) validate the LC-MS/MS method for diagnosis of the patients with IEMs. A total of 570 enrolled healthy participants were divided into 3 age groups, namely, (1) newborns (1-7 days), (2) 8 days–7 years, and (3) 8–17 years, to establish the age-specific cut-offs for AAs and ACs. Also, 273 suspected patients with IEMs were enrolled to evaluate the reliability of the established cut-off values. Quantitation of AAs and ACs was performed on an automated LC-MS/MS system using dried blood spot (DBS) cards. Then the specimens of the enrolled clinically suspected patients were analyzed by the established method. Nine patients came out as screening positive for different IEMs, including two borderline positive cases of medium-chain acyl-CoA dehydrogenase deficiency (MCAD). A second-tier test for confirmation of the screening positive cases was conducted by urinary metabolic profiling using gas chromatography- mass spectrometry (GC-MS). Out of 9 cases that came out as screening positive by LC-MS/MS, seven cases were confirmed by urinary GC-MS analysis including 3 cases with phenylketonuria, 1 with citrullinemia type II, 1 with methylmalonic acidemia, 1 with isovaleric acidemia and 1 with carnitine uptake defect. Two borderline positive cases with MCAD were found negative by urinary GC-MS analysis. In conclusion, along with establishment of a validated LC-MS/MS method for quantitation of AAs and ACs from the DBS cards, the study also demonstrates the presence of predominantly available IEMs in Bangladesh.